Atypical Outcomes for Hepatitis-associated Acquired Aplastic Anemia: 2 Case Studies and Review of the Literature. Issue 5 (18th July 2021) - Lapinski, Jillian; Nolfi-Donegan, Deirdre; Cooper, James D.; Squires, Robert H.
Abstract : There is little data specifically dedicated to the long-term outcomes of the hepatitis-associated variant of aplastic anemia (HAAA). A majority of patients with nonsevere (moderate) aplastic anemia progress to severe aplastic anemia, and severe aplastic anemia typically results in death if left untreated. We present 2 unique cases of HAAA that contribute to our knowledge of the natural history of this disease variant. One patient had moderate HAAA that never progressed to severe disease. The second patient had severe HAAA that spontaneously resolved without treatment. The rare possibility of moderate HAAA failing to progress to fulfill severe criteria, or of severe HAAA spontaneously improving, may complicate early treatment decisions for some patients.